Printable organic light-emitting diodes for next-generation visible light communications: a review - Guo, Kunping; Tang, Zhe; Chou, Xingxing; Pan, Saihu; Wan, Chunchen; Xue, Tao; Ding, Liping; Wang, Xiao; Huang, Jin; Zhang, Fanghui; Wei, Bin (Advanced Photonics Nexus, 2023)
Visible light communication (VLC) is an emerging technology employing light-emitting diodes (LEDs) to provide illumination and wireless data transmission simultaneously. Harnessing cost-efficient printable organic LEDs (OLEDs) as environmentally friendly transmitters in VLC systems is extremely attractive for future applications in spectroscopy, the internet of things, sensing, and optical ranging in general. Here, we summarize the latest research progress on emerging semiconductor materials for LED sources in VLC, and highlight that OLEDs based on nontoxic and cost-efficient organic semiconductors have great opportunities for optical communication. We further examine efforts to achieve high-performance white OLEDs for general lighting, and, in particular, focus on the research status and opportunities for OLED-based VLC. Different solution-processable fabrication and printing strategies to develop high-performance OLEDs are also discussed. Finally, an outlook on future challenges and potential prospects of the next-generation organic VLC is provided.